Human rights infringement against contemporary legal practice in several criminal cases - Rydz-Sybilak, Katarzyna (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
Issues connected with protection against tortures or other forms of inhuman or degrading treatment are regulated in the European law not only in The Convention for the Protection of Human Rights and Fundamental Freedoms, but also in The Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment, which was adopted by The Committee of Ministers of the Council of Europe on June 26, 1987 and later ratified by all 47 countries of The Council of Europe. It is a key element in amending the control system. It has been agreed that the system based on individual and international pleas should be supported by preventive measures. Various situations in which the state has serious obligations so as to protect art. 3 of the Convention, take place following criminal proceedings by organs entitled to act according to legislation. It ought to be mentioned that despite our country’s ratification of the above mentioned legal acts, while conducting pre-trial proceedings in criminal cases, the violation of basic human rights and inhumane treatment of the suspects or the accused happen the most often. The state is responsible for securing proper conditions that would grant respect for one’s dignity and the procedures and methods of obtaining incriminating evidence are not to cause suffering whose scale and intensity would surpass needs of personal security of the accused or suspects during the proceedings in criminal trials, with respect to the legal procedures regulating the arrest and the use of preventative measures in form of a detention order.